Natural dye plants for buton woven fabric in Wabula Village, Buton District - Birman, Birman; Andarias, S. Hafidhawati; Slamet, Agus (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2024)
This study aims to document the species and parts of plants, processing, and colours produced in the dyeing process of Buton woven fabrics. The research was conducted in July-October 2019. The method used was descriptive-qualitative through observation and interviews with 30 weaving crafters in Wabula Village, Buton Regency. Data were analysed by descriptive analysis. The results showed that the plants used were the leaves and stems of tarum (Indigofera tinctoria L.) to get blue colour, jackfruit stems (Artocarpus heterophyllus L.) to get brown colour, noni roots (Morinda citrifolia L.) to get light red colour, turmeric rhizome (Curcuma longa L.) to get light yellow and reddish brown, stems and roots of bitti (Vitex cofassus R.) to get yellow colour, and bark of mahogany (Swietenia mahagoni (L.) Jacq) to get reddish brown colour. The colours were obtained through the steps of dyeing woven fabrics consisting of extraction of materials by fermentation or boiling methods, mordanting, dyeing, and colour fixation. The four types of fixators used are acetic acid, iron (Fe), lime, and  alum. The motifs formed on Buton fabrics have their own meanings and uses for the Wabula people.